Effect of extender supplemented with date palm pollen grain on caprine semen qualities - Ng Pui Sie (2022)
Date Palm Pollen Grain (DPPG) were proved to maintain semen characteristics and quality in bulls, equines and buffaloes. However, DPPG as supplementation in the extender for goats are scarce. Hence, the aims of this experiment were 1) to investigate the semen motility and viability and 2) to examine the functional membrane integrity of semen in different concentrations of DPPG supplemented in goat semen extenders. In this study, DPPG was added in tris-citrate-fructose-yolk (TCFY) semen extender with 0%, 4% and 8% of concentration and chilled at 5oC for 0 hour, 24 hours and 48 hours. DPPG was absence in control group. The diluted semen samples were assessed for sperm motility, viability and membrane integrity. A total of four ejaculations from two Boer bucks were used in this study. The results indicated that the ability to maintain sperm viability was significantly higher in the extender supplemented with 8% DPPG in all storage times (P<0.05). Plus, 8% of DPPG in extender significantly improved sperm motility after 48 hours (56.67±5.57) compared to 0% DPPG and 4% DPPG (40.83±3.00 vs 43.33±5.24), respectively. Results also showed that sperm membrane integrity percentage in 8% DPPG (40.00±4.04) was significantly higher than 0% DPPG (30.33±2.19) at 0-hour storage time. Overall, the extender supplemented with 8% DPPG assisted in maintaining sperm quality after 24 hours of chilled storage (P<0.05). Thus, the findings revealed that 8% of DPPG supplemented in semen extenders proved to maintain viability, motility and membrane integrity compared to control.